TRADE PERSPECTIVE AND AGRICULTURE POLICY PERSPECTIVE IN INDONESIA - Yona Wahyu Lolita; Syahrul Ibad; Musdalifah Musdalifah (Universitas Halu Oleo, 2020)
Agriculture market offering with liberal global market as a consequence of the opening for the economy in Indonesia. Liberalization is due to unilateral policies and international trade agreements including both tariffs and non-tariffs. The purpose of this study is to determine Trade Perspective And Agriculture Policy Perspective In Indonesia . The methode that was used in the research is library research approach, this study means the whole activity of collecting some library data, reading making a note and analyzing of the research. The results of the study explain that agricultural producing countries as developing countries are at a disadvantage or receive very little profit from international trade. Liberalization can have detrimental effects that can threaten the domestic market and the interests of other staff concerned about the welfare of producer farmers and food security. This can occur due to production errors of resource ownership, mastery of technology, economic development and the government's commitment to the focus of the agricultural sector.